Pengaruh pengungkapan ESG, earning per share, dan book value per share terhadap harga saham pada perusahaan indeks IDX30 (2020-2023) - Rahayu Dwi Putri; Dessi Susanti (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
The research aims to determine whether the disclosure of Environmental Social Governance (ESG), Earnings per Share (EPS), and Book Value per Share (BVPS) influences stock prices. Companies listed in the IDX30 index from 2020 to 2023 were sampled using a purposive sampling technique. Multiple linear regression analysis techniques were carried out using the SPSS version 26 application. The results of the analysis show that ESG and EPS disclosure do not influence stock prices, whereas BVPS has a significant and positive effect. In addition, simultaneously, Environmental Social Governance (ESG), Earnings per Share (EPS), and Book Value per Share (BVPS) have a significant effect on stock prices.